A Study on the Instability of the Surrounding Rock Mass of the Roadway Under Disturbing Load - Hui Xu; Wankui Bu; Jun Qiu; Long Ma; Hao Qin; Yajun Li; Weishe Zhang; Pengxiang Li; Dong Zhang; Peng Li; Chen Jia (Energy Science & Engineering)
ABSTRACT The rock burst is one of the major dynamic disasters in deep underground engineering, such as coal mining, and has become a significant technical challenge urgently requiring solutions in rock mechanics and engineering. In the related research, there are many reports on the stability analysis of the laminar split structure under static loads and few reports on the stability analysis under dynamic loads. This paper addresses the stability of surrounding rock in deep roadways, focusing on the key factor of disturbed load. First, the paper theoretically establishes the control equation for analyzing the dynamic stability of the laminar split structure in the coal wall of roadway, deriving the minimum critical load for instability of the laminar split structure under two constraint conditions: simply supported at both ends and fixed at both ends. Second, using discrete element software, the paper analyzes the influence of disturbing load on the stability and energy accumulation characteristics of the surrounding rock of the roadway. It examines the variation patterns of stress in the surrounding rock, deformation of both sides and roof‐floor, distribution of plastic zones, and energy accumulation characteristics with respect to time t and the intensity of disturbing load pmax. Finally, the paper analyzes the stability of surrounding rock in a mine involved in a rock burst accident. The research results provide a basis and reference for analyzing the risk of rock burst under similar conditions.